Optimizing the Application of Technology through the Application of the Baznas Information Management System (Simba) in Zakat Management at the Baznas of North Sumatra Province - Marliyah Marliyah; Fadilah Andriani (Fakultas Ekonomi Universitas Dehasen Bengkulu, 2022)
The development of the digital world in Indonesia is currently growing rapidly. The rapid development of the digital world is accompanied by developments in Information Technology. One of the efforts that has been made by BAZNAS ProvSu in assisting the management of zakat is by applying information technology through the application of the BAZNAS information management system (SIMBA). However, there are several obstacles in optimizing the application of SIMBA in zakat management, such as the limited ICT skills possessed by zakat managers and the internet network which is sometimes less supportive. The formulation of the problem in this study is how to optimize the application of technology through the application of the BAZNAS Information Management System (SIMBA) in the management of zakat at BAZNAS ProvSu and what are the supporting and inhibiting factors for the application of technology through the application of the BAZNAS Information Management System (SIMBA) in the management of zakat at BAZNAS ProvSu. The research objectives in this study were to determine the optimization of the application of technology through the application of the BAZNAS Information Management System (SIMBA) in the management of zakat at BAZNAS ProvSu and to determine the supporting and inhibiting factors for the application of technology through the application of the BAZNAS Information Management System (SIMBA) in the management of zakat at BAZNAS ProvSu. . The research method in this research is to use a qualitative research type with a descriptive approach. Data collection techniques used are observation, interviews and documentation. Data analysis techniques by collecting and reviewing all data, data reduction, compiling data and checking the validity of the data. The results showed that the implementation of the SIMBA application at BAZNAS ProvSu in zakat management had not yet run optimally. Supporting factors in optimizing the application of the samba application in zakat management at BAZNAS ProvSu such as the quality of HR in the IT field, internet networks and laptops and computers. In addition, the inhibiting factors come from internal and external parties.